2013
DOI: 10.1021/cn400016d
|View full text |Cite
|
Sign up to set email alerts
|

GluN2A and GluN2B NMDA Receptor Subunits Differentially Modulate Striatal Output Pathways and Contribute to Levodopa-Induced Abnormal Involuntary Movements in Dyskinetic Rats

Abstract: Dual probe microdialysis was used to investigate whether GluN2A and GluN2B NMDA receptor subunits regulate striatal output pathways under dyskinetic conditions. The preferential GluN2A antagonist NVP-AAM077 perfused in the dopamine-depleted striatum of 6-hydroxydopamine hemilesioned dyskinetic rats reduced GABA and glutamate levels in globus pallidus whereas the selective GluN2B antagonist Ro 25-6981 elevated glutamate without affecting pallidal GABA. Moreover, intrastriatal NVP-AAM077 did not affect GABA but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 54 publications
0
13
0
1
Order By: Relevance
“…The lack of effect of Ro 25-6981 could be because of an insufficient dosage or it is also possible that a transient surge in either 5-HT or glutamate in the mPFC could have been missed because of dilution effects in the 20-min dialysate sample. Alternatively, the effects of Ro 25-6981 may be area specific because it has been reported that this compound increases dialysate glutamate in other brain areas such as the globus pallidus (Mabrouk et al, 2013). Furthermore, it is also known that stereotypies produced by MK-801 do not result from changes in prefrontal cortex activity .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of effect of Ro 25-6981 could be because of an insufficient dosage or it is also possible that a transient surge in either 5-HT or glutamate in the mPFC could have been missed because of dilution effects in the 20-min dialysate sample. Alternatively, the effects of Ro 25-6981 may be area specific because it has been reported that this compound increases dialysate glutamate in other brain areas such as the globus pallidus (Mabrouk et al, 2013). Furthermore, it is also known that stereotypies produced by MK-801 do not result from changes in prefrontal cortex activity .…”
Section: Discussionmentioning
confidence: 99%
“…At the end of each epoch, the predominant behavior was rated as immobility, climbing, and swimming by an experimenter blind to the treatment. As these drugs allegedly possess a fast antidepressant action and display similar pharmacokinetic profiles in microdialysis studies (Mabrouk et al, 2013), their administration was carried out 20 min before the test session.…”
Section: Behavioral Measuresmentioning
confidence: 99%
“…Using the BAC-TRAP approach [63], Heiman et al [64] have shown how remarkably complex these changes in dSPN gene expression are. Although it has been widely assumed that sensitized D1R signaling was necessary for these adaptations with chronic L-DOPA treatment, work by Alcacer et al [65] has questioned this proposition, pointing to the probable importance of NMDAR signaling through Ras [66-68]. …”
Section: What Goes Wrong In L-dopa Induced Dyskinesia?mentioning
confidence: 99%
“…Moreover, PSD-95, which has been recently shown to mediate LID [8], promotes the phosphorylation of NMDARs by Fyn [14]. The NR2B subunit is critical in the regulation of the glutamate NMDAR and therefore in the development of LID [15,16]. Indeed, a clinical trial with the NR2B antagonist CP-101,606 has been proven to reduce LID despite its side effects [17].…”
Section: Introductionmentioning
confidence: 99%